2010
DOI: 10.1093/jmedent/47.4.581
|View full text |Cite
|
Sign up to set email alerts
|

γ Ray Dosimetry and Mating Capacity Studies in the Laboratory on Aedes albopictus Males

Abstract: In Italy, Aedes albopictus Skuse is currently recognized as the most dangerous mosquito, and as currently applied conventional control methods gave unsatisfactory results, we are developing alternative strategies such as the sterile insect technique. To find the optimal sterilizing dose, male pupae were exposed to different doses of gamma rays in the range 20-80 Gy, generated by a Cesium-137 source. The effects of male pupal age at irradiation and gamma ray dose on adult male emergence, sterility level, longev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
98
2
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(118 citation statements)
references
References 28 publications
12
98
2
6
Order By: Relevance
“…This radiation dose represents the best compromise between the expected level of sterility and mating competitiveness. Consistent with evidence from our previous laboratory and semi-field investigations [78, 24], the radiation dose (35 Gy) currently applied to sterilize Ae . albopictus males is expected to induce 95–97% sterility.…”
Section: Discussionsupporting
confidence: 88%
“…This radiation dose represents the best compromise between the expected level of sterility and mating competitiveness. Consistent with evidence from our previous laboratory and semi-field investigations [78, 24], the radiation dose (35 Gy) currently applied to sterilize Ae . albopictus males is expected to induce 95–97% sterility.…”
Section: Discussionsupporting
confidence: 88%
“…albopictus eggs produced by ENEA was amplified by mass-rearing at ENEA Casaccia (Rome) and Centro Agricoltura Ambiente G. Nicoli (CAA, Crevalcore, Bologna) based on standard operating procedures developed at CAA. 33 The resulting eggs were then hatched at ENEA Casaccia following the protocol described in Balestrino et al 33 Larval rearing trays were set up starting with 2000 first-instar larvae (larval density of two larvae/mL deionized water) at 28 ∘ C, 80% relative humity (RH) and a 14:10 h light/dark photoperiod. Larvae were fed for 4 days with increasing doses (0.2, 0.4, 0.6 and 0.8 mg/larva/day) of a liquid diet consisting of 50% tuna meal, 36% bovine liver powder, 14% brewer's yeast and 0.2% w/v vitamin mix (IAEA-BY diet).…”
Section: Arwp Male Production and Sexingmentioning
confidence: 99%
“…The newly emerged males must go through the holes to take flight. at 30 Gy at the Medical Physics Department of St. Anna Hospital (Ferrara, Italy), just before release (Balestrino et al, 2010).…”
Section: Mosquito Rearing and Sugar Feeding Devicementioning
confidence: 99%
“…Domestication may lead to abnormal behaviors in laboratory reared insects (Bartlett, 1984); indeed one study found that after just 9-16 weeks of colonization males Culex tarsalis were unable to compete for wild females (Reisen et al, 1982). The exposure to ionizing radiation commonly used to sterilize mosquitoes for use in the SIT causes somatic damage which may affect ability to perform well in the field (Helinski et al, 2009) though the dose and timing can be adjusted to minimize the negative effects (Balestrino et al, 2010). In the context of mosquito control strategies relying on the release of male adults which must disperse, find and successfully mate with wild females, such as the SIT, it is of crucial importance to formulate optimal larval diets in order to produce sterile males which are highly competitive with wild males.…”
Section: Introductionmentioning
confidence: 99%